Improved Quality of Services with Intelligent MAC in Wireless Sensor Networks for Mission Critical Applications - Halkai, Abhijit; Terdal, Sujatha; Bhasgi, Shivani (Asian Journal of Electrical Sciences, 2022)
Wireless sensor networks are very feasible to monitor where human reach is impossible. But conserving the limited resource and maintaining Quality of service is the challenging task. There is most need to design an algorithm to maintain quality of services. In this paper we have designed node layered division MAC with adaptive listening based on the queue size at the transmitting cluster node. The proposed protocol attenuates the problem of collision and unfair distribution of power among the nodes. When compared with the existing algorithms, IQMAC outperforms in terms of network lifetime, delay, PDR and collision probability.